Entrepreneurs’ attitudes toward seasonality in the tourism sector - Martín Martín, José María; Guaita Martínez, José Manuel (International Journal of Entrepreneurial Behaviour and Research, 2020)
Purpose: The purpose of this paper is to investigate the factors that condition decision making by entrepreneurs in the tourism sector. Specifically, the authors consider whether the decisions related to seasonal closure are conditioned by non-economic factors related to quality of life. Design/methodology/approach: The study uses data from a survey of entrepreneurs in two highly seasonal tourist locations in Spain: one coastal destination and one mountain destination. The information provided by the survey was used to determine the factors that condition the decision to close for part of the year and to analyze the way in which entrepreneurs evaluate the costs and benefits associated with the period of closure. Findings: The results show that entrepreneurs acknowledge the cost of shutting down during the off-peak season. However, although they recognize this cost, other elements are important in their decision making such as the quality of life of the entrepreneur, the presence of a more profitable secondary activity in a different destination and the tenure regime of the business. Entrepreneurs attach great importance to factors that justify the closure of establishments for several months a year. This, in turn, means that public policies designed to reduce the intensity of seasonality lose effectiveness. Originality/value: This paper sheds light on whether there are underlying non-economic motives that lead to a shutdown during the off-peak season. There are no previous studies that analyze the influence of the decision to close and which consider aspects related to the quality of life of entrepreneurs. Therefore, the study presents the first analysis of entrepreneurs’ assessments of the costs and benefits of a seasonal resting period.
Keywords: entrepreneurs; profitability; quality of life; seasonality; Spain; tourism industry; Scopus; JCR